2020
DOI: 10.1021/acs.biomac.0c00824
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Enzymes within Polymersomes by Coencapsulation of Trehalose

Abstract: Enzymes are essential biocatalysts and very attractive as therapeutics. However, their functionality is strictly related to their stability, which is significantly affected by the environmental changes occurring during their usage or long-term storage. Therefore, maintaining the activity of enzymes is essential when they are exposed to high temperature during usage, or when they are stored for extended periods of time. Here, we stabilize and protect enzymes by co-encapsulating them with trehalose into polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…Interestingly, it was found that natural enzymes in polymeric nanoreactors could be highly stabilized by co‐encapsulation with trehalose. [ 33 ] For this case, even though laccase‐loaded polymeric nanoreactors were incubated at 50 °C for three weeks, 75% original activity of laccase was still maintained under the protection of trehalose.…”
Section: Design and Construction Of Polymeric Nanoreactorsmentioning
confidence: 99%
“…Interestingly, it was found that natural enzymes in polymeric nanoreactors could be highly stabilized by co‐encapsulation with trehalose. [ 33 ] For this case, even though laccase‐loaded polymeric nanoreactors were incubated at 50 °C for three weeks, 75% original activity of laccase was still maintained under the protection of trehalose.…”
Section: Design and Construction Of Polymeric Nanoreactorsmentioning
confidence: 99%
“…However, in some cases, the enzyme encapsulation efficiency is relatively low, making the process uneconomical. 34 Moreover, when embedded in a polymer matrix, the diffusion of the substrate is restricted, resulting in overall decreased activity. 35 The mechanism by which trehalose protects proteins is still under debate, but the most popular hypotheses are as follows:…”
Section: ■ Introductionmentioning
confidence: 99%
“…49,50 This can reduce the incidence of solute crystallization during storage, which is often held responsible for the damages on the protein. 34,51 However, trehalose does not always play a dramatic role in enzyme protection. For example, in the stabilization of β-galactosidase against lyophilization, trehalose was found to have a similar protective effect as poly(ethylene glycol) (PEG), 28 which is known for its disappointing stabilizing ability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Nico Bruns reports on polymersome encapsulation of trehalose alongside enzymes in order to stabilize enzyme activity. 17 In this way, functional enzyme activity is maintained in spite of prolonged periods of time under desiccation as well as upon exposure to elevated heats. Julie Champion then describes work to create vesicles from recombinant fusion proteins containing elastin-like polypeptides.…”
mentioning
confidence: 99%